Molecular Analysis of Liquid Vitreous Biopsy Reveals Occult Lymphoma Following Cytology-Negative Biopsies of the Brain and Vitreous - Balikov, Daniel A.; Conway, Kyle; Brown, Noah A.; Camelo-Piragua, Sandra; Rao, Rajesh C. (Ocular immunology and inflammation, 2024)
Primary central nervous system lymphoma (PCNSL) is a rare but deadly malignancy that principally affects adults in the fifth and sixth decades of life. Despite diagnostic advances in analyses of cerebral spinal fluid and neuroimaging, definitive diagnosis of PCNSL requires primary brain tissue biopsy. While small neurosurgical biopsy volumes are pursued to minimize removal of normal brain tissue, the spatial margins to precisely biopsy pathologic tissue are narrow and can result in missed diagnoses. Furthermore, prior steroid treatment can significantly reduce tumor burden increasing the likelihood of a non-diagnostic biopsy. A retrospective case report from a tertiary referral center using a combination of neuroradiological studies, sterotactic tissue biopsy, and molecular testing for genome mutations. A 72-year-old woman with strong suspicion for PCNSL clinically and radiologically, but cerebral spinal fluid and primary brain tissue biopsy were negative for tumor. However, vitreous liquid biopsy molecular testing for a mutation as well as B-cell clonality ( rearrangement) were positive, indicating the presence of secondary vitreoretinal lymphoma from PCNSL. Only after autopsy of her brain was histopathological and immunohistochemical evidence of PCNSL confirmed. This case illustrates the unique contribution of liquid biopsy neuropathology-oriented molecular testing in a challenging case with high clinical suspicion of PCNSL in which gold-standard diagnostic testing failed to yield a diagnosis.